(untitled) (Research, Society and Development, 2022)
The consumption of alcoholic beverages is a practice, in which it is inserted in society, being classified as the most used psychoactive substance in the world. Thus, university students are seen as a vulnerable group for the use of alcoholic beverages, justified by the exhausting workload, stress and decreased leisure time. Thus, the objective of this study is to explore the factors associated with the consumption of alcoholic beverages by medical students. This study is an integrative review with a descriptive and exploratory nature and a qualitative approach. Data collection was carried out between July and September 2022 using the CAPES Periodicals Portal as a database. The initial search generated a total of 475 articles, but after applying the eligibility criteria, only 8 articles were included in the review. The studies selected in the review aimed to assess the prevalence and factors associated with the consumption of alcoholic beverages among medical students. Therefore, in view of the study, it is concluded that the level of alcohol consumption among young medical students is high because it is directly linked to the pressure they suffer.